Role of Teneurin C-Terminal Associated Peptides (TCAP) on Intercellular Adhesion and Communication - Dodsworth, Thomas L.; Lovejoy, David A. (Frontiers in Neuroscience, 2022)
The teneurin C-terminal associated peptides (TCAP) are encoded by the terminal exon of all metazoan teneurin genes. Evidence supports the liberation of a soluble TCAP peptide either by proteolytic cleavage from the mature transmembrane teneurin protein or by a separately transcribed mRNA. Synthetic versions of TCAP, based on its genomic structure, are efficacious at regulating intercellular communication by promoting neurite outgrowth and increasing dendritic spine density in vitro and in vivo in rodent models. This is achieved through cytoskeletal re-arrangement and metabolic upregulation. The putatative receptors for TCAPs are the latrophilin (LPHN) family of adhesion G-protein coupled receptors, which facilitate TCAP’s actions through G-proteins associated with cAMP and calcium-regulating signalling pathways. The teneurin/TCAP and latrophilin genes are phylogenetically ancient, likely serving primitive functions in cell adhesion and energy regulation which have been since adapted for a more complex role in synaptogenesis in vertebrate nervous systems.